An account of Ceropegia sect. Chamaesiphon (Apocynaceae) in Moçambique with new records and two new species - Bruyns, Peter V.; Klak, Cornelia; Hanáček, Pavel (Phytotaxa, 2018)
Two new species of Ceropegia sect. Chamaesiphon H.Huber from Moçambique, C. cyperifolia Bruyns and C. gracilidens Bruyns, are described and illustrated. A brief account of eight other species recorded for the first time from Moçambique is given and notes are provided on the little-known Ceropegia simplex (Schltr.) Bruyns, which has not been collected since Schlechter’s original gathering in 1898. A key is presented to all 11 species in Moçambique. Brachystelma simplex subsp. banforae Lebrun & Stork from West Africa is raised to specific level as Ceropegia banforae (Lebrun & Stork) Bruyns so that Ceropegia simplex is confined to material from Moçambique. Ceropegia vahrmeijeri (R.A.Dyer) Bruyns is reduced to synonymy under C. cupulata (R.A.Dyer) Bruyns and Brachystelma mortonii C.C.Walker under Ceropegia plocamoides (Oliver) Bruyns.